Case report and literature review: Hemophagocytic lymphohistiocytosis in a pregnant woman with systemic lupus erythematosus with Syntaxin 11 gene defect - Ren, Wei; Yang, Siyuan; Liu, Haiying; Pan, Zhenglun; Li, Zhao; Qiao, Peng; Ma, Hui (Frontiers in Oncology, 2022)
Hemophagocytic lymphohistiocytosis is an extremely rare occurrence during pregnancy. Early recognition of its signs and symptoms is critical for early intervention, and delays in diagnosis may be life-threatening. A 23-year-old nulliparous woman presented with a persistent fever as high as 39°C with bilateral edema of the lower limbs at 24 weeks of gestation. Typical laboratory findings included pancytopenia, high triglycerides, ferritin, transaminases, bilirubin, and hypoproteinemia. Active systemic lupus erythematosus was diagnosed using an autoimmune work-up and a Systemic Lupus Erythematosus Disease Activity Index 2000 score of 17 points. Her bone marrow aspirate revealed prominent hemophagocytosis; hence, HLH was confirmed. Genetic tests showed mutations in Syntaxin 11 mutations. Considering the potential impact of drugs on the fetus, the patient and her family members chose to terminate the pregnancy through medical induction of labor. Afterwards, her condition improved with immunosuppressive therapy.